Solar Cell System Design for Mechanical Cooling System on the Ferry 500 GT - Danny, Faturachman; Shariman, Mustafa; Yoseph, Arya Dewanto; Muswar, Muslim (2014)
Nowadays electricity is a primary need for almost the entire human race. Electrical energy is very instrumental in our capability to carry out various economic activities. Electric energy can be produced from a variety of sources. Energy can be categorized into two kinds: energy that can be renewable and energy that cannot be renewed. Source of energy that cannot be renewed among others are derived from fossil and nuclear systems. Energy that can still be renewed among others derived from geothermal (solar energy), ocean waves, waterfalls, wind, etc. Source of energy that cannot be renewed; notably energy derived from fossil, are gradually becoming unsustainable because oil price are getting more expensive and the amount of energy are extracted from sources that are already depleted. Energy from the sun can be used for heating (solar thermal) or generate electricity (photovoltaic). Utilization of solar energy from solar photovoltaic plants as a source of electrical energy produces no pollution to the environment. The basic ingredient of photovoltaic system is solar cell. Installation of solar cells on a vessel can be used as energy source to be utilized in a variety of electrical equipments on the ship. Relatively abundance of sun energy that will never run out must be harvested because the sunshine exposure on the territory of Indonesia is around 10 to 12 hours daily. In this case, solar cells are used to meet the needs of the mechanical cooling equipments on board of the ferry that sails around the region of Indonesia. Expected usage from this solar energy source can reduce the usage of fossil fuels and resulted in considerable saving on the overall ferry operational costs.